Respuesta :
Answer:
6 = −4x + y
−5x − y = 21
Answer: (-3, -6)
2x + y = 20 6x – 5y = 12
Answer:
(7 , 6)
Step-by-step explanation:
Solve the system of equations by substitution.
6 = −4x + y --> y = 4x + 6
−5x − y = 21
Substitute y = 4x + 6 into −5x − y = 21
−5x − (4x + 6) = 21
-5x - 4x - 6 = 21
-9x = 27
x = - 3
y = 4(-3) + 6
y = -12 + 6
y = -6
(-3, -6)
Solve the system by the elimination method.
2x + y = 20
multiply the equation by (-3) ; 2x + y = 20 so
-6x - 3y = - 60
6x – 5y = 12
------------------add
-8y = - 48
y = 6
2x + y = 20
2x + 6 = 20
2x = 14
x = 7
(7 , 6)